2018
DOI: 10.1001/jamaoto.2018.0658
|View full text |Cite
|
Sign up to set email alerts
|

Association of Idiopathic Sudden Sensorineural Hearing Loss With Affective Disorders

Abstract: This cohort study suggests that ISSNHL is associated with an increased incidence of affective disorders, specifically depression and anxiety. Therefore, these findings suggest that clinicians should monitor patients with ISSNHL carefully, and take specific precautions to reduce their risk of depression and anxiety disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 24 publications
5
38
0
2
Order By: Relevance
“…It was reported that the incidence of severe depressive disorder is higher in the hearing impaired patients than in the general population [16]. Consistently with this hypothesis, depressive disorder is more common in patients who do not recover after ISSHL [3]. The current evidence suggests that psychological disorders such as depression and anxiety have a negative effect on the quality of life of patients with SSHL [3].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It was reported that the incidence of severe depressive disorder is higher in the hearing impaired patients than in the general population [16]. Consistently with this hypothesis, depressive disorder is more common in patients who do not recover after ISSHL [3]. The current evidence suggests that psychological disorders such as depression and anxiety have a negative effect on the quality of life of patients with SSHL [3].…”
Section: Discussionsupporting
confidence: 72%
“…Consistently with this hypothesis, depressive disorder is more common in patients who do not recover after ISSHL [3]. The current evidence suggests that psychological disorders such as depression and anxiety have a negative effect on the quality of life of patients with SSHL [3]. The authors of this study reported that clinicians increased the risk of ISSHL to develop affective disorders in patients, suggesting that special measures should be taken to reduce the risk of depression and anxiety disorder [3].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Dysfunction of the inner ear causes vertigo, hearing loss, and tinnitus in patients, leading to physical and functional impairment that is further associated with anxiety, social isolation, and cognitive decline (Jacob and Furman, 2001;Lin et al, 2011a;Bisdorff et al, 2013;Contrera et al, 2017;Kim et al, 2018). A number of pathologies, such as vestibular neuritis and sudden sensorineural hearing loss, have acute onset and lead to permanent impairments of inner ear function (Kuhn et al, 2011;Manzari et al, 2013) through degeneration of the sensory epithelium, primary nerves, and their synaptic connections, as documented in postmortem tissue samples from patients (Rauch, 2001;Merchant et al, 2005;Richard and Linthicum, 2012).…”
Section: E Inner Ear Diseasesmentioning
confidence: 99%